BANKING INVESTMENT ACTIVITY AND REGIONAL INDUSTRIAL DEVELOPMENT: EVIDENCE FROM HAMKORBANK ATB TERMIZ BRANCH, UZBEKISTAN - Qulsoatov Jushqin; O.Mirzayev (TADQIQOTLAR, 2026)
Annotation. This study examines the relationship between banking investment activity and regional industrial development, focusing on the experience of Hamkorbank ATB Termiz Branch in Uzbekistan. The research analyzes the role of bank investments in supporting industrial enterprises, stimulating production growth, and enhancing regional economic performance. Special attention is given to the financing mechanisms employed by the bank and their impact on industrial modernization and business expansion.